Resilience in Santri: The Impact of Social Support on the Quran Memorization Journey - Abdullah Azzam Al Afghani; Milcha Fakhria (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
Santri who attend school and simultaneously memorize the Quran in Pondok Pesantren face greater challenges than their peers. This study explores the forms of social support that can improve the resilience of santri who memorize the Quran. This study used a non-experimental quantitative approach involving 180 students in five Islamic boarding schools in Central Java. Hypothesis testing was conducted using Hierarchical Linear Regression. The results showed that emotional support (β=0.306, p<0.01) and informational support (β=0.237, p<0.01) significantly predicted resilience, while instrumental support did not (β=0.154, p>0.05). Furthermore, social support in the form of friendship increased students' resilience to 42.7% (R²=0.427, F(1,175)=9.730, p<0.001). These findings demonstrate the importance of peer support, guidance from religious teachers (kyai), and a supportive environment in the process of memorizing the Quran. This study shows that for Quran memorizers, resilience is strengthened through togetherness, guidance, and emotional support that collectively enable them to face spiritual and academic challenges.